Family cord blood banking for sickle cell disease: a twenty-year experience in two dedicated public cord blood banks - Hanadi Rafii; Françoise Bernaudin; Helene Rouard; Valérie Vanneaux; Annalisa Ruggeri; Marina Cavazzana; Valerie Gauthereau; Aurélie Stanislas; Malika Benkerrou; Mariane De Montalembert; Christele Ferry; Robert Girot; et al. (Haematologica, 2017)
Efforts to implement family cord blood banking have been developed in the past decades for siblings requiring stem cell transplantation for conditions such as sickle cell disease. However, public banks are faced with challenging decisions about the units to be stored, discarded, or used for other endeavors. We report here 20 years of experience in family cord blood banking for sickle cell disease in two dedicated public banks. Participants were pregnant women who had a previous child diagnosed with homozygous sickle cell disease. Participation was voluntary and free of charge. All mothers underwent mandatory serological screening. Cord blood units were collected in different hospitals, but processed and stored in two public banks. A total of 338 units were stored for 302 families. Median recipient age was six years (11 months-15 years). Median collected volume and total nucleated cell count were 91 mL (range 23–230) and 8.6×108 (range 0.7–75×108), respectively. Microbial contamination was observed in 3.5% (n=12), positive hepatitis B serology in 25% (n=84), and homozygous sickle cell disease in 11% (n=37) of the collections. Forty-four units were HLA-identical to the intended recipient, and 28 units were released for transplantation either alone (n=23) or in combination with the bone marrow from the same donor (n=5), reflecting a utilization rate of 8%. Engraftment rate was 96% with 100% survival. Family cord blood banking yields good quality units for sibling transplantation. More comprehensive banking based on close collaboration among banks, clinical and transplant teams is recommended to optimize the use of these units.